An Investigation into the Organisational Challenges Associated with an Ageing and Age Diverse Workforce - Iles, Lucinda J. (Curtin University, 2023)
This thesis aims to understand the challenges and opportunities that come with an ageing workforce. The collection of studies examines processes and outcomes related to inclusion of mature workers, individualised work design, and the integration of age diverse team members. The research makes theoretical and practical contributions to strategies for retaining and engaging mature workers.